Conserved hierarchical gene regulatory networks for drought and cold stress response in Myrica rubra - Xu, Weijie; Ren, Haiying; Qi, Xingjiang; Zhang, Shuwen; Yu, Zheping; Xie, Jianbo (Frontiers in Plant Science, 2023)
Stress response in plant is regulated by a large number of genes co-operating in diverse networks that serve multiple adaptive process. To understand how gene regulatory networks (GRNs) modulating abiotic stress responses, we compare the GRNs underlying drought and cold stresses using samples collected at 4 or 6 h intervals within 2 days in Chinese bayberry (Myrica rubra). We detected 7,583 and 8,840 differentially expressed genes (DEGs) under drought and cold stress respectively, which might be responsive to environmental stresses. Drought- and cold-responsive GRNs, constructed on the basis of the temporal transcriptional patterns in the two abiotic stresses, share common trans-regulators and conserved regulating network. In both GRNs, basic helix-loop-helix family transcription factor (bHLH) serve as central nodes. MrbHLH10 transcripts exhibited continuous increase in the two abiotic stresses and acts upstream regulator of ASCORBATE PEROXIDASE (APX) gene. To examine the potential biological functions of MrbHLH10, we generated transgenic Arabidopsis plants constitutively overexpressing MrbHLH10. Upon exposure to drought and cold stress, compared to wild-type (WT) plants, overexpressing transgenic Arabidopsis plants maintained higher APX activity and biomass accumulation. Consistently, RNAi plants had elevated susceptibility to both stresses. Taken together, these results suggested that MrbHLH10 mitigates abiotic stresses through the modulation of ROS scavenging.